2021
DOI: 10.21608/jssae.2021.153322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizobium inoculant, Nitrogen Starter and Cobalt on Stimulation of Nodulation, N Fixation and Performance of Faba Bean (Vicia faba L.) Grown under Salinity Stress

Abstract: In the modern agriculture systems, there is a general tendency to reduce the amounts of mineral nitrogen inputs and maximize their use efficiency to minimize environmental pollution and its hazards on public human health. It is well known that cobalt is a necessary trace element to leguminous crops and bacterial communities responsible for biological nitrogen fixation (BNF). So, two field trials were performed in a split-split-plot design with three replicates during two-successive winter seasons of 2019/2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
3
9
0
Order By: Relevance
“…This was partly due to reduced nutrient availability under higher pH and competition between these nutrients for transport sites in the root, leading to a reduction in photosynthesis, consistent with previous findings 21 , 22 . These detrimental effects ultimately reflected in the reduction of peanut agronomic traits, peanut yield, and IWUE, which align with previous studies 70 72 . Dang et al 73 also highlighted that plant growth and metabolism vary based on the concentration and state of Co in the rhizosphere and soil.…”
Section: Discussionsupporting
confidence: 89%
“…This was partly due to reduced nutrient availability under higher pH and competition between these nutrients for transport sites in the root, leading to a reduction in photosynthesis, consistent with previous findings 21 , 22 . These detrimental effects ultimately reflected in the reduction of peanut agronomic traits, peanut yield, and IWUE, which align with previous studies 70 72 . Dang et al 73 also highlighted that plant growth and metabolism vary based on the concentration and state of Co in the rhizosphere and soil.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, salinity stress affects seed quality, decreasing protein and starch levels while increasing salt concentration. However, the implementation of appropriate management practices can mitigate the harmful effects of salinity stress on faba bean (Baddour et al 2021).…”
Section: )mentioning
confidence: 99%
“…The results demonstrated that applying cobalt at a rate of 30 mg L -1 yielded the most favorable outcomes in terms of growth, yield attributes, nodule number, nodule weight, and grain yield. In the research by Baddour et al (2021), the combined effect of Rhizobium inoculation, nitrogen application at different rates (100%, 75%, and 50% of the recommended dose), and cobalt supplementation at varying concentrations (0.0, 8.0, and 12.0 mg cobalt L -1 ) was examined using a combined method of soaking and foliar application. The best results were achieved when plants were inoculated with a specific Rhizobium strain, nitrogen was applied at a rate of 15 kg N fed -1 , and cobalt was treated at rates of 8.0 and 12.0 mg cobalt L -1 .…”
Section: B Cobaltmentioning
confidence: 99%
“…Insufficient Mo levels can lead to reduced nodulation and nitrogen fixation, as discussed by Gericó et al (2020). Co and Mo are essential for the vitamin B12 required synthesis for hemoglobin formation in nodules, therefore success N fixation (El-Sherpiny et al 2021). The relationship between copper (Cu) requirements for symbiotic nitrogen fixation and its role in plant growth is not well-defined.…”
Section: Introductionmentioning
confidence: 99%